Um sistema para comunicação nas dependências de instituições usando NODEMCU-VISION - Cunha, Nora Neyse Torres da (2020)
Communication is fundamental for interaction and dialogue between people who live together, allowing to share knowledge and experiences. Thus, this work aims to develop a communication system in the dependencies of the Federal Institute of Amazonas, allowing the exchange of information between servers and students without the need for staff to travel to classrooms, avoiding delays and mishaps in passing communications. It is noticeable that news or reports are being shared every day, but due to the dispersal of students in college, the means by which data must be announced is difficult for all to see simultaneously. In addition, the process of disclosing warnings or breaking news is not publicly transmitted. Currently, the Federal Institute of Amazonas does not have a device that provides the objectives demonstrated by this study, the proposal to create a system for exclusive communication of IFAM between students, servers and teachers of low cost and embedded, which meets the current need for a technology. vision to make the exchange of information agile, planned and effective. The lack of this type of system in school environments emphasizes research and development in the technological area providing continuous improvement in communication processes, due to the concern about the lack of transparency with students and teachers. Thus, the ESP8266 microcontroller, embedded on the NodeMCU hardware platform, is responsible for receiving the JSON file, which interprets by displaying the string (text) in the LED array. This microcontroller is commonly used and has the ability to receive codes via WiFi and is suitable for the project as it uses the IFAM LAN for sending messages. Therefore, with a low cost final product, ease of use and reliability of answers, tests were carried out in classrooms, whose results were satisfactory during the whole process of passing information.